Lead acid battery with high resistance to over‐discharge using graphite based materials as cathode current collector. Issue 6 (1st December 2021) - Okano, Hiroshi; Hano, Yuta; Sugimoto, Kaito; Ohira, Fumiya; Inoue, Takashi; Hosokawa, Toshihiro; Iwai, Taichi; Takai, Shigeomi; Yabutsuka, Takeshi; Yao, Takeshi
Abstract: Lead acid battery has been one of the most important battery for industry use. However, conventional lead acid battery cannot be recharged after over discharge and the performance is greatly declined. It has been revealed that the cause of not being able to be recharged is the formation of α‐PbO2 on the surface of β‐PbO2 cathode active material due to local cell reaction between lead current collector and β‐PbO2 . Formation of α‐PbO2 is prevented by using gold as the current collector. In this study, we developed the lead acid battery with high resistance to over discharge using graphite materials as current collector. The formation of α‐PbO2 was prevented by using expanded natural graphite sheet as cathode current collector. The lead acid battery with current collector of expanded natural graphite sheet containing 5% polypropylene (PP) can repeat deep charge and discharge between 0 and 2 V for more than about 6 months and showed flat potential area between 1.9 and 1.3 V for every cycle. Furthermore, this battery can be charged again after over discharge for more than 4 month at the open circuit. We have succeeded to develop high performance lead acid battery. Abstract : High performance lead acid battery with high resistance to over discharge have been developed. This battery with current collector of graphite sheet containing 5% polypropylene can repeat deep charge and discharge for more than about 6 months. Furthermore, it can be charged again after over discharge for more than 4 month at the open circuit.